Genome-wide identification of WOX family members in nine Rosaceae species and a functional analysis of MdWOX13-1 in drought resistance. (March 2023) - Lv, Jiahong; Feng, Yi; Jiang, Lizhong; Zhang, Guibin; Wu, Ting; Zhang, Xinzhong; Xu, Xuefeng; Wang, Yi; Han, Zhenhai
Abstract: WUSCHEL-related homeobox (WOX) transcription factors (TFs) are important in plant development processes and evolutionary novelties. In this study, a genome-wide comprehensive analysis of WOX genes from nine Rosaceae species was carried out, and their potential roles in Malus were subsequently investigated. 125 WOXs in 9 Rosaceae species were identified and classified into three clades, i.e., the ancient, intermediate, and WUS clades. Prunus. domestica contained the most intra-genomic collinearity among the nine Rosaceae species. Additionally, the cis-elements in WOX gene family members were compared and classified into three categories, including phytohormone-responsive, plant growth and development, and abiotic and biotic stresses. Overexpression (OE) of MdWOX13–1 also increased the callus weight and enhanced ROS scavenging against drought stress. Furthermore, via yeast-one hybrid assay and LUC analyses, MdWOX13–1 could directly bind to the MdMnSOD promoter. Therefore, our results will facilitate further study of the WOX genes' function in the Rosaceae family. Highlights: WUSCHEL-related homeobox (WOX) TFs are important in plant development processes and evolutionary novelties. A genome wide comprehensive analysis of WOX genes from nine Rosaceae species was carried out and 125 WOXs were identified and classified into three clades. MdWOX13-1 could directly bind to the MdMnSOD promoter enhanced ROS scavenging against drought stress.